2023
DOI: 10.1002/chem.202300616
|View full text |Cite
|
Sign up to set email alerts
|

Unique Tubular BiOBr/g‐C3N4 Heterojunction with Efficient Separation of Charge Carriers for Photocatalytic Nitrogen Fixation

Abstract: The industrial ammonia synthesis process consumes a lot of energy and causes serious environmental pollution. As a sustainable approach for ammonia synthesis, photocatalytic nitrogen reduction employing water as the reducing agent has a lot of potential. A simple surfactant‐assisted solvothermal method is used to synthesize g‐C3N4 nanotubes with flower‐like spherical BiOBr grown inside and outside (BiOBr/g‐C3N4, BC). The hollow tubular structure realizes the full use of visible light by the multi‐scattering ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…It is commonly recognized that the efficiency of semiconductor photocatalysis is greatly influenced by the separation and transport of photogenerated carriers. , A series of photoelectrochemical characterization tests were performed on F-TiO 2 , MCS, and F-TiO 2 /MCS catalysts to examine their photogenerated charge separation and transfer behaviors. Figure a displays the transient photocurrent response of F-TiO 2 , MCS, and F-TiO 2 /MCS.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly recognized that the efficiency of semiconductor photocatalysis is greatly influenced by the separation and transport of photogenerated carriers. , A series of photoelectrochemical characterization tests were performed on F-TiO 2 , MCS, and F-TiO 2 /MCS catalysts to examine their photogenerated charge separation and transfer behaviors. Figure a displays the transient photocurrent response of F-TiO 2 , MCS, and F-TiO 2 /MCS.…”
Section: Resultsmentioning
confidence: 99%
“…Xue et al reported that the photocatalytic nitrogen fixation performance of BiOBr was improved about 10 times by the synergistic effect of oxygen vacancy and ultra-thin layer structure [84]. Gao et al loaded the flower-like BiOBr onto the inner and outer sides of the C3N4 nanotubes simultaneously, effectively realizing the separation of photogenerated electrons and hole pairs, and thus increasing the photocatalytic nitrogen fixation activity of BiOBr by 13.9 times [85]. Now, photocatalytic nitrogen fixation capacities of BiOX are still unlikely to replace the Haber-Bosch process, but their potentials are huge and need In fact, pure BiOX exhibited low performance of photocatalytic nitrogen fixation.…”
Section: Photocatalytic Nitrogen Fixationmentioning
confidence: 99%
“…[27] Based on the above advantages, Bi-based materials are considered to be a promising candidate for photocatalytic NRR. The Bi-based NRR catalysts currently studied are of a wide variety, including metal Bi, [28,29] BiO 2-x , [30] Bi 2 S 3 , [31] BiOX (X=F, Cl, Br and I), [32][33][34] BiVO 4 , [35] (BiO) 2 CO 3 [36] and pentavalent bismuthate M(BiO 3 ) n (n = 1, M=Li, Na, K, Ag; n = 2, M=Mg, Zn, Sr, Ba, Pb) . [37,38] Zhang et al [39] synthesized Bi nanosheets by electrochemical reduction method as NRR electrocatalyst, which showed a high Faraday efficiency of 10.46 � 1.45 % at À 0.8 V (RHE).…”
Section: Introductionmentioning
confidence: 99%